ANALYSIS PERFORMANCE ORGANIZATION OF COMPETENCY ASSESSMENT UNIT BKD PROVINCE OF CENTRAL JAVA IN THE IMPLEMENTATION OF THE ASSESSMENT CENTER - Ayu Atika; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
So far, Civil Servants are often assumed to be less professional employees. This was due, among other things, to a mismatch between the competencies of civil servants and job competencies that they held. Seeing how urgent the competency role of a civil servant in carrying out his duties, BKD Province of Central Java captures this as a challenge that needs to be faced. This was done, among others, through the establishment of an assessment center at the Competency Assessment Unit by BKD Province of Central Java as a form of follow-up on competency-based HR development. The problem faced by the Competency Assessment Unit BKD Province of Central Java is that there is still frequent rejection at the request of the regional assessment. The research method used in this study is descriptive qualitative. The theory used is the theory of performance measurement from Dwiyanto, which is five indicators which include: Productivity, Service Quality, Responsiveness, Responsibility, Accountability. The results of this study indicate that the organizational performance of the Competency Assessment Unit Province of Central Java can be said to be quite good, which is dominating problems is namely the limited infrastructure to support performance and the limited number of human resources that are not increasing but are always decreasing every year due to retirement, so the thing that can be do is to improve the infrastructure used to support performance in the implementation of the assessment center. Keywords: